2014
DOI: 10.1051/mbcb/2014026
|View full text |Cite
|
Sign up to set email alerts
|

Épidémiologie des traumatismes dento-maxillo-faciaux au CENHOSOA Antananarivo

Abstract: Résumé -Introduction : L'objectif de cette étude est d'analyser les caractéristiques épidémiologiques des fractures dento-maxillo-faciales à Antanarivo (Madagascar). Méthodologie : Il s'agit d'une étude rétrospective de janvier 2003 à août 2012. Les dossiers retenus relatent des traumatismes dento-maxillo-faciaux chez des patients admis au centre hospitalier de Soavinandriana (CENHOSOA) Antananarivo. Résultats : Sur les 166 dossiers colligés, le sexe masculin prédominait (83,1 %) et l'âge le plus prévalent se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Regarding rhinoscopy, isolated post-traumatic epistaxis was more common, with a significant incidence of 34.42%, followed by fractures of the nasal bones without displacement, at 30.60%, and nasal contusion, representing 19.13%. Moreover, similar studies conducted by researchers in Madagascar [12] reported 59.6% epistaxis, while in France [13], a frequency of 61.8% for nasal fractures was observed. Regarding lesions in the pharynx, larynx, and oral cavity, the majority were represented by dental avulsions at 52%, followed by dental fractures at 28%, and tongue lacerations at 12%.…”
Section: Discussionmentioning
confidence: 53%
“…Regarding rhinoscopy, isolated post-traumatic epistaxis was more common, with a significant incidence of 34.42%, followed by fractures of the nasal bones without displacement, at 30.60%, and nasal contusion, representing 19.13%. Moreover, similar studies conducted by researchers in Madagascar [12] reported 59.6% epistaxis, while in France [13], a frequency of 61.8% for nasal fractures was observed. Regarding lesions in the pharynx, larynx, and oral cavity, the majority were represented by dental avulsions at 52%, followed by dental fractures at 28%, and tongue lacerations at 12%.…”
Section: Discussionmentioning
confidence: 53%